1982
DOI: 10.1017/s1323358000021391
|View full text |Cite
|
Sign up to set email alerts
|

L1642 — A Dust Cloud in a Cometary Globule?

Abstract: Lynds 1642 is a small, somewhat insignificant dark cloud centred at 04h33, — 14°20 (1950). On a IIIaJ UKSTU Schmidt plate it may be seen to lie within an approximately circular patch of nebulosity which we believe to be visible by reflection. Its galactic location (l = 210°.9 b = -36°.5) places it beneath the local arm in the direction of Orion and it is likely that it is seen by reflection of the integrated light of the stars in that region of the galaxy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…This is in good agreement with the direct measurement and we adopt 140 pc for the distance of L1642. Based on previous multiwavelength data (Liljeström & Mattila 1988;Taylor et al 1982;Laureijs et al 1987;Liljeström 1991) L1642 appears as a cool and quiescent cloud. It is associated with a much larger HI cloud (over 4…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is in good agreement with the direct measurement and we adopt 140 pc for the distance of L1642. Based on previous multiwavelength data (Liljeström & Mattila 1988;Taylor et al 1982;Laureijs et al 1987;Liljeström 1991) L1642 appears as a cool and quiescent cloud. It is associated with a much larger HI cloud (over 4…”
Section: Introductionmentioning
confidence: 90%
“…in the 100 µm IRAS map. Furthermore, HI data shows a velocity gradient along the tail, with increasing velocity towards the northeast (Taylor et al 1982). This suggests that the first PMF component represents the very head of the whole structure, and gas in the head is flowing relative to the rest of the structure, not only towards the south-west but also more towards us.…”
Section: Summary Of Kinematics and Environmental Effectsmentioning
confidence: 96%
“…The view of L1642 has changed from a "small, somewhat insignificant cloud" (Taylor et al 1982) to an interesting object in several aspects, as shown by the various studies already mentioned. So far, B-1 and B-2 are the only known stars associated to L1642.…”
Section: Star Formation In L1642mentioning
confidence: 99%
“…The overall kinematics is explained by a cometary structure where the low-velocity gradients on the western side may be a result of a geometry, where on that side of the cloud the gas is flowing mainly in the plane of the sky. Taylor et al (1982) predicted that the shearing flow will enhance the density towards the head of the cometary cloud, increase turbulence in the outer parts, and can lead to the formation of hydrodynamical instabilities.…”
Section: Structure and Evolution Of L1642mentioning
confidence: 99%
“…Taylor et al (1982) made HI observations of a region adjacent to and including L 1642. They suggested that L 1642 is a result of hydrodynamic instability within a larger cometary cloud.…”
Section: Introductionmentioning
confidence: 99%